Artistic values of the components of space Natural History Museum (Al-Academy, 2016)
The artistic concepts differ in their expressive and semantic relations, among these concepts are the artistic values, as there are points of view, social concepts and historical values interacted from one generation to another over the time. These values represent symbols and indications reflect reality, which has passed through the time to reach us with environmental forms saved by the history at the Natural History Museum, has an impact on the receives mind with its formal and sensory dimensions and connecting with that history as an environment that lacks to the current reality which has immortal means particularly in the cognitive thinking , and the reflection of that in the Iraqi culture and with the associated concepts of interior design to highlight the effectiveness of artistic values at the creative level